Chronic diseases and allergies are risk factors predictive of a history of Medial Tibial Stress Syndrome (MTSS) in distance runners: SAFER study XXIV - Boer, P.-H.; Schwellnus, M. P.; Jordaan, E. (The Physician and Sportsmedicine, 2023)
Background Medial Tibial Stress Syndrome (MTSS) is one of the most common causes of exercise-associated lower leg pain in distance runners.